Android tourist translator (Indonesian to English) - Tan, Md. Muzamir (2014)
Tourism is an industry that is booming and rapidly growing around the world. For some countries, this industry is essential for economic growth. Countries all around the world are taking extra measures and making greater efforts to promote tourism.